PRES in pregnancy: MRI and it’s role in decision making - Valecha, Shalini Mahana; Koshish, Sara Azad; Rajesh Gandhewar, Manisha; Dhingra, Divija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Posterior reversible encephalopathy syndrome (PRES) is an alarming clinic-neuro-radiological syndrome accompanying various clinical conditions, presenting with headache, encephalopathy, seizures, cortical visual disturbances or blindness. The lesions in PRES are thought to be due to vasogenic oedema, predominantly in the water-shed regions of the posterior cerebral hemisphere, fortunately, completely reversible with management of the primary condition. We report a case of primigravida with 26 weeks pregnancy, who presented with acute, severe, in-tractable, throbbing headache, tingling sensation in the posterior neck and upper shoulder region, photophobia, nausea and mild pre-eclampsia. Standard therapy did not relieve the headache, BP remained fluctuant, so migraine/some intra-cranial pathology was suspected. MRI is the gold-standard diagnostic modality. It revealed the classical acute PRES picture. PRES implies breaching of the blood brain barrier, resultant cerebral edema and potential for further intra-cranial events of serious proportions. Notably, PRES may be seen with normotension. Pregnancy was terminated un-eventfully, recovery was prompt and complete. Two weeks later, the patients showed marked improvement clinically and neuro-imaging features of PRES had dis-appeared.